The Impact of Peer-centred Feedback on Academic Essay Writing: A Mixed-Methods Study of Third-Year English Students at Imam Al-Kadhum College - Hussain Jaber, Asmaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Students who learn English as a foreign language (EFL) in college must know how to write academic essays. However, despite several years of formal English education, several Iraqi EFL students still find it difficult to develop effective academic essay writing capabilities (AEWC). This is, largely, due to pedagogical, linguistic, and contextual limitations. As such, the present study examined the impact of peer-centred feedback (PCF) on the AEWC of third-year EFL students from the English Department of the Imam Al-Kadhum College in Baghdad, Iraq. A total of 120 students were equally divided into two groups, namely, an experimental group (60 students) and a control group (60 students). Over a two-month period, the experimental group received structured PCF on their academic essays, while the control group received traditional teacher-centred feedback (TCF). A mixed-methods approach, which combined quantitative data, derived from the pre- and post-intervention techniques, and qualitative data, derived from the distributed questionnaires and various semi-structured interviews, was used. The post-intervention test scores indicated that the experimental group performed better than the control group. Therefore, structured PCF positively impacted the students’ AEWC. Apart from that, the data collected from the questionnaire and semi-structured interviews indicated that the students perceived PCF as highly motivating, helpful, and collaborative, which improved their confidence, awareness of mistakes in their essays, and their learner autonomy. Therefore, the findings of the present study empirically indicate the importance of using PCF in an Iraqi EFL settings, as well as the practical implications of using PCF in academic essay writing (AEW) courses for Iraqi EFL students. DOI: https://doi.org/10.54633/2333-024-056-002